Synthesis of finite length multi level sequences for clutter rejection in radar - Siti Julia, Rosli; Farid, Ghani, Prof. Dr.; Alif Hasmani, Abd Ghani; R. Badlishah, Ahmad, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/